Study of Comparison of conventional ultrasound, RMI 4 score and CT imaging in diagnosis of Ovarian Cancer confirmed by surgical-pathological findings - Baniya, Sebina; Shrestha, Binuma; Acharya, Bijay Chandra; Gurung, Sarita; Subedi, Hem Nath; Pandey, Manju; Tiwari, Shristi; Thapa, Pramila (Nepalese Journal of Cancer, 2023)
Background: Ovarian cancer; 5th commonest cancer among Nepalese women is the leading cause of gynecologic cancer related death. Proper diagnostic studies therefore assist Gyne-oncologist for appropriate surgery and chemotherapeutic planning, there by optimizing the patient prognosis. Objective of current study was to compare ultrasonography imaging, CT imaging, CA 125 value, RMI 4 score and surgical staging in diagnosis of ovarian cancer correlated with histo-pathological findings. Materials and Methods: The study was retrospective observational study, carried out between 14th April 2019 to 16th October 2021, in the department of surgical oncology (Gynecology oncology unit), B.P Koirala Memorial Cancer Hospital, Bharatpur. Results: 53 patient data were included in the observation. The efficacy of Ultrasound (sensitivity-90.90%, Specificity-60%) and CT (sensitivity-100%, specificity-65%) gave the best result in non-invasive investigations; whereas surgical staging (sensitivity- 96.96%, specificity- 90%) gave the better result when invasive modalities were considered. RMI 4 score had sensitivity 96.96% and specificity 60%. Conclusion: All modalities had good diagnostic performances and complemented each other in further defining the characterization of the ovarian mass, local spread and distant tumor dissemination.